2023
DOI: 10.1021/acsami.3c09659
|View full text |Cite
|
Sign up to set email alerts
|

LEGO-like Assembly of Fibrous Modules for Display Textiles

Seonjeong Lee,
Won Seok Cho,
Kyung Gook Cho
et al.

Abstract: Due to their promising advantages over classical rigid devices, the development of display textiles has exciting potential for various fields, including sensor technology, healthcare, and communication. To realize display textiles, it is necessary to prepare light-emitting building blocks at the fiber level and then weave or knit them to form the desired textile structures. However, from a practical viewpoint, it is difficult to continuously weave functional fibers containing light-emitting devices using conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In recent years, devices based on transparent amorphous oxide semiconductors (AOS) have received much more attention as an alternative material to silicon for various devices. [ 416 ] Among various AOS materials, amorphous InGaZnO4$\text{InGaZnO}_{4}$ (a‐IGZO) has been utilized in various device applications such as biosensors, [ 417 ] phototransistors, [ 418 ] and nonvolatile memories. [ 419 ] The primary reason for wide range of applications is due to superior optical and electrical characteristics, higher field‐effect mobility, and superior spatial uniformity.…”
Section: Nonsilicon Channel Materials For Isfet Ph Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, devices based on transparent amorphous oxide semiconductors (AOS) have received much more attention as an alternative material to silicon for various devices. [ 416 ] Among various AOS materials, amorphous InGaZnO4$\text{InGaZnO}_{4}$ (a‐IGZO) has been utilized in various device applications such as biosensors, [ 417 ] phototransistors, [ 418 ] and nonvolatile memories. [ 419 ] The primary reason for wide range of applications is due to superior optical and electrical characteristics, higher field‐effect mobility, and superior spatial uniformity.…”
Section: Nonsilicon Channel Materials For Isfet Ph Sensorsmentioning
confidence: 99%
“…[ 419 ] The primary reason for wide range of applications is due to superior optical and electrical characteristics, higher field‐effect mobility, and superior spatial uniformity. [ 416,420 ] IGZO‐based ISFETs have been reported recently. [ 124 ] In one of the literature, it has been reported that a‐IGZO based channel DG ISFET with Al2$_{2}$O3$_{3}$‐sensing film shows a pH sensitivity of 347.6 mV/pH, beyond the Nernstian limit.…”
Section: Nonsilicon Channel Materials For Isfet Ph Sensorsmentioning
confidence: 99%
See 1 more Smart Citation